(untitled) - Martin, Jacqueline (Oxford, 2010)
Read and discover all about Wild Weather. How are polar bears adapted to living in a frozen ecosystem? What are decomposers? This exciting new series of non-fiction readers provides interesting and educational content, with activities and project work. The readers are graded at four levels, from 3 to 6, suitable for students from age 8 and older
Keywords: Thời tiết,English language,Weather,Tiếng Anh; Văn học thiếu niên,Reading comprehension,Juvenile literature,Đọc hiểu